Production and quality of guava fruits ’Pedro Sato’ submitted to different pruning times - Hojo, Ronaldo Hissayuki; Chalfun, Nilton Nagib Jorge; Hojo, Ellen Toews Doll; Veiga, Ruben Delly; Paglis, Carlos Maurício; Lima, Luiz Carlos de Oliveira (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to verify the possibility of fruit production at different periods, according to the pruning time (September and December 2003 and March and June 2004). The experimental design was a randomized blocks with guava plants of cultivar Pedro Sato per repetition, with four-years old, no defoliation, and branches prunned with 30 cm length. Evaluations consisted of: number of fruits per plant, plant yield, firmness, soluble solids (SS), titratable acidity (AT), SS/AT ratio, pH and total soluble sugars. It was observed that the pruning periods affected these characteristics. The fruit number per plant varied from 269.8 to 500.8. Fruit weight (186.9 to 205.5 g) was inversely proportional to the yield per plant. The total yield weight of fruits varied from 55.5 to 93.6 kg per plant. The pruning period also influenced significantly physio-chemical characteristics of the fruits, but not the fruit firmness. It is possible to produce high quality guava fruits during nine months of the year by prunning plants in the periods above mentioned.